2020
DOI: 10.1111/ppl.13280
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of a novel cold and drought regulatory‐protein encoding CORA‐like gene, SbCDR, induced osmotic tolerance in transgenic tobacco

Abstract: A potent cold and drought regulatory-protein encoding gene, SbCDR was cloned from an extreme halophyte Salicornia brachiata. In vitro localisation study, performed with SbCDR::RFP gene-construct revealed that SbCDR is a membrane protein. Overexpression of the SbCDR gene in tobacco plants confirmed tolerance against major environmental constraints such as salinity, drought and cold, as evidenced by improved chlorophyll contents, plant morphology, plant biomass, root length, shoot length and seed germination eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 82 publications
4
17
0
Order By: Relevance
“…Seeds of SbERD4 overexpressing transgenic lines (L2, L13, L14, L15, and L18), vector control (VC), and wild-type (WT) plants were kept on MS media for germination under control (no additional supplementation) and stress conditions (by supplementing 200 mM NaCl for salinity or 300 mM mannitol for osmotic/drought) for 21 days, and the seed-germination percentage was calculated [ 30 , 31 ]. Different growth parameters, including root (RL) and shoot (SL) length, fresh (Fw) and dry (Dw) weight were calculated and compared with control (WT and VC) plants grown under salinity (200 mM NaCl) and osmotic/drought (300 mM mannitol) stress conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of SbERD4 overexpressing transgenic lines (L2, L13, L14, L15, and L18), vector control (VC), and wild-type (WT) plants were kept on MS media for germination under control (no additional supplementation) and stress conditions (by supplementing 200 mM NaCl for salinity or 300 mM mannitol for osmotic/drought) for 21 days, and the seed-germination percentage was calculated [ 30 , 31 ]. Different growth parameters, including root (RL) and shoot (SL) length, fresh (Fw) and dry (Dw) weight were calculated and compared with control (WT and VC) plants grown under salinity (200 mM NaCl) and osmotic/drought (300 mM mannitol) stress conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The fresh weight (Fw) of leaf samples of transgenic and control (WT and VC) plants (treated and untreated) was recorded, and samples were incubated in deionized water for 24 h. After incubation, turgid weight (Tw) was measured, which was followed by dry weight (Dw) measurement at 40 °C. The percentage of relative water content (RWC) was calculated [ 30 ] by the following equation: …”
Section: Methodsmentioning
confidence: 99%
“…A transgenic plant that performed better compared to other lines was selected for the differential transcript expression profiling 62 , 70 . Forty-two days old plant grown under N 2 starvation (21 days) stress condition and a plant (42-days old) subjected to NaCl (150 mM for 24 h) stress were used for microarray analysis along with corresponding control plants.…”
Section: Methodsmentioning
confidence: 99%
“…Increased levels of the glutathione metabolite, γ-aminobutyric acid (GABA), as well as accumulation of β-cyanoalanine, a byproduct of ethylene biosynthesis, were observed in the DREB1A transgenic lines [45] (Table 2). Nicotiana tabacum NMR Chlorogenic acid, 4-O-caffeoylquinic acid, malic acid, threonine, alanine, glycine, fructose, β-glucose, α-glucose, sucrose, fumaric acid and salicylic acid [49] N. tabacum GC-MS 4-Aminobutanoic acid, asparagine, glutamine, glycine, leucine, phenylalanine, proline, serine, threonine, tryptophan, chlorogenic acid, quininic acid, threonic acid, citric acid, malic acid and ethanolamine [50] Oryza sativa GC-MS Glycerol-3-phosphate, citric acid, linoleic acid, oleic acid, hexadecanoic acid, 2,3-dihydroxypropyl ester, sucrose, 9-octadecenoic acid, 2,3-dihydroxypropyl ester, sucrose, mannitol and glutamic acid [44] O. sativa LC-MS Tryptophan, phytosphingosine, palmitic acid, 5-hydroxy-2-octadenoic acid 9,10,13-trihydroxyoctadec-11-enoic acid and ethanolamine [51] Populus…”
Section: Involvement Of Metabolomics In Genetically Modified (Gm) Cropsmentioning
confidence: 99%
“…Metabolomic profiling also demonstrated that introduction of the cold and drought regulatory-protein encoding CORA-like gene (SbCDR) from S. brachiata into tobacco could enhance salt and drought tolerance by increasing the stress related metabolites such as proline, threonine, valine, glyceric acid, fructose, 4-aminobutanoic acid, asparagine [50]. Overexpression of a native UGPase2 gene induced several metabolites related to amino acid, phenolic glycosides such as asparagine, γ-amino-butyric acid, aspartic acid, glutamine, 5-oxo-proline, 2-methoxyhydroquinone-1-O-glucoside, 2-methoxyhydroquinone-4-O-glucoside, salicylic acid-2-O-glucoside, 2,5-dihydroxybenzoic acid-5-O-glucoside, salicin in transgenic Populus lines [52].…”
Section: Techniques Key Metabolites Referencesmentioning
confidence: 99%